New SAR Algorithm Based on Orthogonal Projections for MMT Detection and Interference Reduction - Brigui, Frederic; Thirion-Lefevre, Laetitia; Ginolhac, Guillaume; Forster, Philippe (IEEE transactions on geoscience and remote sensing, 2014)
We develop a new synthetic aperture radar (SAR) algorithm based on physical models for the detection of a man-made target (MMT) embedded in strong interferences (trunks of a forest). These physical models for the MMT and the interferences are integrated in low-rank subspaces and are based on scattering and polarimetric properties. Several images, called subspace SAR images, can be generated and combined considering these subspace models. We then propose a new approach for target detection and interference reduction based on the combination of SAR subspace images. We show that our SAR algorithm outperforms the classical SAR imagery algorithm on both simulated data and real data in the context of foliage penetration detection.